Analysis of Soybean Raw Material Inventory Control Using the Economic Order Quantity (EOQ) Method at the Terang Tofu Factory - Kusno Hadidjija; Dina Fitriana; Lazuardi Lazuardi (Journal of Evrímata: Engineering and Physics, 2025)
Kebonagung Terang Tofu Factory is one of the famous tofu industries in Pasuruan City. This business produces raw tofu. This research aims to determine the optimal amount of soybean raw material inventory that the Kebonagung Terang Tofu Factory must have, the right time for repurchasing soybean raw materials, the optimal purchase frequency, and the optimal total ordering costs for procuring soybean raw materials at the Terang Tofu Factory. Kebonagung, Pasuruan City. This research is quantitative descriptive, which describes how the company controls raw material inventories through analysis of the data obtained. The analysis methods used include Economic Order Quantity (EOQ) to determine the optimal amount of raw material purchases, Re-Order Point (ROP) to determine the right time for repurchasing raw materials, annual purchase frequency, Safety Stock (SS) to determine the amount safety stock that the company must have, and Total Inventory Cost (TIC) to determine the company's total storage costs. The results of the analysis using the EOQ method show that the Kebonagung Terang Tofu Factory should order 62,740 kg of soybean raw materials in 2024 with an order frequency of 7 times, ROP of 7.956 kg, Safety Stock of 5,874 kg, and total storage costs of Rp. 172.535.